Correlation and Regression Analysis Between Visitors and Buyers to The Selling Nominal Using Least Square - Sovia, Nanum; Karisma, Ria Dhea Layla Nur (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.661, 2017)
Regression and correlation analysis is used to know the relationship between independent variable and dependent variable. This research uses data of 19 respondent data which include independent variable on visitors  and buyers , and dependent variable of selling nominal . The model used in this research is Multiple Linear Regression. The result of the equation is . The result of F test is calculated result of F value equal to  with alpha  meaning that variable of visitor and buyer influence to nominal variable of selling nominal. While the Individual test shows that value visitor < Significance value , t value buyer < Significance value  =  that the t value on the visitor less than the Significance value which means the decision for the test received . While the value of t arithmetic on the Buyer is also less than the significance value for the test receive . Then it can be concluded that there is no significant influence on the partial test. Correlation between visitors with buyers is significant. On the otherhand, there is a significant correlation between the buyer and the nominal purchase. Also, there is a significant correlation of the buyer with the nominal purchase there is a significant correlation. So it can be concluded that the influence between variables considered above have significant correlation value.